Trends in Contraceptive Use Worldwide 2015 - United Nations (United Nations, 2016)
Comprehensive and timely estimates on global trends in family planning are critical for assessing current and future contraceptive demand and setting policy priorities to ensure universal access to sexual and reproductive health and the realization of reproductive rights. This report presents a concise, descriptive analysis of levels and trends in key family planning indicators from Model-based Estimates and Projections of Family Planning Indicators 2015 and the data set World Contraceptive Use 2015, representing 195 countries or areas. The Population Division of the Department of Economic and Social Affairs of the United Nations Secretariat provides regular updates of the estimates and projections of family planning indicators as part of its contribution to global monitoring of progress on internationally-agreed targets to achieve universal access to sexual and reproductive health.